Association Between Particulate Matter Exposure and Chronic Rhinosinusitis - Ji-Sun Kim; Dong Chang Lee (Journal of Rhinology, 2023)
Chronic rhinosinusitis (CRS) is a relatively common inflammatory disease of the nasal and paranasal sinus mucosa. Several epidemiological studies have established an association between particulate matter (PM) and CRS. Based on those data, PM has emerged as an important environmental factor in the development of CRS. Recent research has investigated the mechanisms and treatment options for CRS caused by PM through cellular experimentation. Therefore, the authors would like to explain the definition of PM, present research investigating the relationship between PM and CRS, and summarize the involved mechanisms reported to date.